Assessing the impact of peripheral mega retail centres on traditional urban shopping centres - Aloys Borgers; Sanne van Swaaij; Ingrid Janssen (Belgeo)
Recently, retail planning policy in the Netherlands has become much more liberal, probably stimulating the development of new (types of) out-of-town retail centres. This raises the question whether these new out-of-town retail centres will threaten existing retail centres. The purpose of this paper is to present a method to assess the likely effects of new peripheral retail centres on existing retail structures.The method is based on the stated choice approach. Different realizations of an imaginary peripheral mega shopping centre are presented to respondents. The respondents have to estimate the number of times each existing shopping centre and the new imaginary peripheral centre would have been visited if the imaginary centre had existed. The following variables were used to define the imaginary peripheral retail centre: supply of six branches, distance from home to the peripheral centre, price-product quality ratio, design and ambiance, and entertainment. The results show that depending on its characteristics, a peripheral mega centre can have severe impact on existing shopping centres.